Epicarp interface - Baharuddin, Nasir; Rahmat, Mohd Hafizad (University Putra Malaysia, 2012)
This installation tries to place the natural medium of form in picturing the possibilities through which we interpret information artifacts. The presentation enables semiotic construction that simultaneously leverages the means of production embodied by particular media elements. The recombination of genetic codes of meaning from ‘natural objects representation’ creates hybrid forms through the scientific culture of representing as new form of visual knowledge. The reason is to develop the interactive artifact and introduce “self-interpretation and communication” about creative medium. This addresses browsing creatively, with the disciplinary framework of agrobiologic where the skin of fruits as interface metaphor.